The Prevalence and Risk Factors of Diabetic Maculopathy in Type 2 Diabetes Mellitus: A Study From Central Nepal - Munakarmi, Nilam; Pokharel, Amrit; Malla, Om Krishna; Pradhananga, Chhabindra Lal (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: Diabetic maculopathy is a complication of type 2 diabetes mellitus. This study was done to assess the prevalence and risk factors of Diabetic maculopathy in type 2 diabetes mellitus in Nepalese patients presenting to our hospital. MATERIAL AND METHODS: A hospital-based, descriptive, cross-sectional study was conducted at the department of ophthalmology, Kathmandu Medical College Teaching Hospital (KMCTH), Sinamangal, Kathmandu, Nepal from August, 2012 to October, 2014. 200 patients with type 2 diabetes mellitus underwent a detailed interview and a comprehensive dilated ocular evaluation by an ophthalmologist. Diabetic maculopathy was defined according to the international classification and grading system. RESULTS: 200 patients suffering from type 2 diabetes mellitus included 90 men (45%) and 110 women (55%) of age ranging from 23 80 years (mean age = 56.23, median age = 57.5 and SD = 10.83). Diabetic maculopathy was detected in 22 patients (11%). The disease duration of 6 to 15 years had the highest prevalence of Diabetic maculopathy. Significant risk factors for diabetic maculopathy were higher levels of HbA1c (p = 0.005), higher values of blood pressure (p = 0.001), higher cholesterol levels (p = 0.000), higher LDL-cholesterol levels (p = 0.000), higher triglyceride levels (p = 0.000), higher creatinine values (p = 0.000), higher urea values (p = 0.000), higher FBS levels (p = 0.020), higher PPBS levels (p = 0.001) and lower hemoglobin values (p = 0.000). CONCLUSION: Significant risk factors for diabetic maculopathy were higher levels of HbA1c, higher values of blood pressure, higher cholesterol levels, higher LDL-cholesterol levels, higher triglyceride levels, higher creatinine values, higher urea values, higher FBS levels, higher PPBS levels and lower hemoglobin values. However, smoking, drinking alcohol, dietary habits, HDL and BMI contributed as insignificant risk factors. Journal of Universal College of Medical Sciences (2016) Vol.04 No.01 Issue 13, Page: 16-21